Technology in the delivery room supporting the neonatal healthcare provider's task. Issue 5 (October 2022) - Cramer, Sophie J.E.; Kuypers, Kristel L.A.M.; Martherus, Tessa; Dekker, Janneke; te Pas, Arjan B.
Abstract: Very preterm infants are a unique and highly vulnerable group of patients that have a narrow physiological margin within which interventions are safe and effective. The increased understanding of the foetal to neonatal transition marks the intricacy of the rapid and major physiological changes that take place, making delivery room stabilisation and resuscitation an increasingly complex and sophisticated activity for caregivers to perform. While modern, automated technologies are progressively implemented in the neonatal intensive care unit (NICU) to enhance the caregivers in providing the right care for these patients, the technology in the delivery room still lags far behind. Diligent translation of well-known and promising technological solutions from the NICU to the delivery room will allow for better support of the caregivers in performing their tasks. In this review we will discuss the current technology used for stabilisation of preterm infants in the delivery room and how this could be optimised in order to further improve care and outcomes of preterm infants in the near future.